Metal Ion Chelates as Surrogates of Nucleobases for the Recognition of Nucleic Acid Sequences: The Pd2+ Complex of 2,6-Bis(3,5-dimethylpyrazol-1-yl)purine Riboside - Taherpour, Sharmin; Lönnberg, Tuomas (Journal of Nucleic Acids, 2012)
A 2,6-bis(3,5-dimethylpyrazol-1-yl)purine ribonucleoside has been prepared and incorporated as a conventionally protected phosphoramidite into a 9-mer 2′-O-methyl oligoribonucleotide. According to 1H NMR spectroscopic studies, this nucleoside forms with Pd2+ and uridine a ternary complex that is stable at a micromolar concentration range. CD spectroscopic studies on oligonucleotide hybridization, in turn, suggest that the Pd2+ chelate of this artificial nucleoside, when incorporated in a 2′-O-methyl-RNA oligomer, is able to recognize thymine within an otherwise complementary DNA strand. The duplex containing thymidine opposite to the artificial nucleoside turned out to be somewhat more resistant to heating than its counterpart containing 2′-deoxycytidine in place of thymidine, but only in the presence of Pd2+. According to UV-melting measurements, replacement of 2′-O-methyladenosine with the artificial nucleoside markedly enhances hybridization with a DNA target, irrespective of the identity of the opposite base and the presence of Pd2+. With the thymidine containing DNA target, the Tm value is 2–4°C higher than with targets containing any other nucleoside opposite to the artificial nucleoside, but the dependence on Pd2+ is much less clear than in the case of the CD studies.